Aplicações entre 3-variedades Sol e números de Nielsen para coincidências - Panzarin, Karen Regina (Universidade Federal de São Carlos, 2017)
Let MA be the torus bundle over S1 obtained using as gluing map an Anosov matrix A. In this work we discuss maps from MA to MD and compute the coincidence Nielsen numbers for some families of such maps, moreover we use that such manifolds are double covers of torus semi-bundles and compute the coincidence Nielsen number for selfmaps of Sol 3-manifolds which are torus semi-bundles.
Keywords: 3-variedades Sol; Números de Nielsen; Matemática; CIENCIAS EXATAS E DA TERRA::MATEMATICA